2021
DOI: 10.26811/peuradeun.v9i2.588
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Readiness of Islamic Education Teachers in Innovative Teaching and Learning

Abstract: The importance of Islamic education in building generations and society is undeniable. The field of Islamic education is not static but is constantly evolving as time goes by. In this paper, the author explored the technological innovations in today's world of education as well as the effects of Islamic Education teachers. The paper also discussed the barriers to implement technological education in Islamic education. Because of the current advent and emerging developments of technology and the impact of globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, modern Islamic educational institutions and integrated Islamic educational institutions continuously carry out an inventory of existing human resources, therefore, the basis for recruitment planning is clear. Inventorying human resources is an important thing to do because having an inventory of human resources is a benchmark for recruiting needed human resources [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Planning Of Human Resource Recruitment In Islamic Educationa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, modern Islamic educational institutions and integrated Islamic educational institutions continuously carry out an inventory of existing human resources, therefore, the basis for recruitment planning is clear. Inventorying human resources is an important thing to do because having an inventory of human resources is a benchmark for recruiting needed human resources [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Planning Of Human Resource Recruitment In Islamic Educationa...mentioning
confidence: 99%
“…Islamic educational institutions, especially in Indonesia, in various studies have concluded that institutions are slow in responding to the times [32][33][34][35]. The slow response of Islamic educational institutions to the development of the times often causes the use of the curriculum to no longer match the needs of students [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these madrasas are often lagging behind in adopting more modern and effective learning methods that have been widely applied in other educational institutions. Other constraints such as lack of training and technical support, as well as resistance to new changes among madrasah educators and managers, have also contributed to the slow penetration of educational technology in the Madrasah environment (Suhid et al, 2021). All of this is a significant obstacle to be overcome to ensure that the madrasah is able to adapt to the needs of contemporary education and prepare its pupils for the face of a global digital age (Haddar et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%
“…In Indonesia, Islamic religious education is held in schools by providing freedom and facilities that allow educators to be creative in packaging learning using various methods, strategies, media, and platforms connected to the internet and other supporting technologies. The problem of the quality of Islamic religious education learning in Malaysia also seeks a solution using knowledge integrated with technology, internet media, and various methods (Nawi et al, 2012;Suhid et al, 2021;Kamarazaman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%